EFhd2 Affects Tau Liquid–Liquid Phase Separation - Vega, Irving E.; Umstead, Andrew; Kanaan, Nicholas M. (Frontiers in Neuroscience, 2019)
The transition of tau proteins from its soluble physiological conformation to the pathological aggregate forms found in Alzheimer’s disease and related dementias, is poorly understood. Therefore, understanding the process that modulates the formation of toxic tau oligomers and their conversion to putative neuroprotective neurofibrillary tangles will lead to better therapeutic strategies. We previously identified that EFhd2 is associated with aggregated tau species in AD brains and the coiled-coil domain in EFhd2 mediates the interaction with tau. To further characterize the association between EFhd2 and tau, we examined whether EFhd2 could affect the liquid-liquid phase separation properties of tau under molecular crowding conditions. We demonstrate that EFhd2 alters tau liquid phase behavior in a calcium and coiled-coil domain dependent manner. Co-incubation of EFhd2 and tau in the absence of calcium leads to the formation of solid-like structures containing both proteins, while in the presence of calcium these two proteins phase separate together into liquid droplets. EFhd2’s coiled-coil domain is necessary to alter tau’s liquid phase separation, indicating that protein-protein interaction is required. The results demonstrate that EFhd2 affects the liquid-liquid phase separation of tau proteins in vitro, suggesting that EFhd2 modulates the structural dynamics of tau proteins.